2018
DOI: 10.3390/s18124240
|View full text |Cite
|
Sign up to set email alerts
|

Bowel Sounds Identification and Migrating Motor Complex Detection with Low-Cost Piezoelectric Acoustic Sensing Device

Abstract: Interpretation of bowel sounds (BS) provides a convenient and non-invasive technique to aid in the diagnosis of gastrointestinal (GI) conditions. However, the approach’s potential is limited by variation between BS and their irregular occurrence. A short, manual auscultation is sufficient to aid in diagnosis of only a few conditions. A longer recording has the potential to unlock additional understanding of GI physiology and clinical utility. In this paper, a low-cost and straightforward piezoelectric acoustic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 33 publications
(62 reference statements)
3
28
0
Order By: Relevance
“…Abdominal sounds were recorded using a Zoom H6 Handy recorder (Zoom, Tokyo, Japan) attached to 4 piezo-based sensors placed on the 4 quadrants of the abdomen and held in place with stretchy Tubigrip, together referred to as the “belt.” Software was developed for the initial preprocessing that identified bowel sounds for extraction. This system has previously been described following use for recordings of bowel sounds and detection of the migrating motor complex (MMC) (17).…”
Section: Methodsmentioning
confidence: 99%
“…Abdominal sounds were recorded using a Zoom H6 Handy recorder (Zoom, Tokyo, Japan) attached to 4 piezo-based sensors placed on the 4 quadrants of the abdomen and held in place with stretchy Tubigrip, together referred to as the “belt.” Software was developed for the initial preprocessing that identified bowel sounds for extraction. This system has previously been described following use for recordings of bowel sounds and detection of the migrating motor complex (MMC) (17).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, this design would be very effective to harvest acoustic energy from surrounding noise. Du et al [148] designed an acoustic piezoelectric sensing device using a lowcost technique (Figure 24c). The device is compared with an electronic stethoscope (Litmann 3200), and an almost similar performance was observed (Figure 24c,i).…”
Section: Png Devices For Acoustic Energy Harvestingmentioning
confidence: 99%
“…In recent years, with the development of artificial intelligence technology and wearable medical devices, a lot of AIassisted diagnoses using medical imaging and electronic medical record data have been proved to be effective in reducing workload for doctors. By contrast, the absence of stereophonic data has prevented the auscultation process from being digitized, with only a small number of datasets collected by electronic stethoscopes for research, such as ICBHI[1], Physionet [2] and the Noisy Guts project [3]. [3] explored the use of bowel sounds to characterize IBS with a view to diagnostic use using a diagnostic case-control study, and Independent testing demonstrated 87% sensitivity and 87% specificity for IBS diagnosis using the 15 IBS and 15 healthy participants.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the absence of stereophonic data has prevented the auscultation process from being digitized, with only a small number of datasets collected by electronic stethoscopes for research, such as ICBHI[1], Physionet [2] and the Noisy Guts project [3]. [3] explored the use of bowel sounds to characterize IBS with a view to diagnostic use using a diagnostic case-control study, and Independent testing demonstrated 87% sensitivity and 87% specificity for IBS diagnosis using the 15 IBS and 15 healthy participants. In connection with the work of this article, Our original intention is to mine information about our body and provide helpful information for doctors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation